Analogy and Comparatism: A Response to G.E.R. Lloyd, Fortunes of Analogy. Issue 3 (3rd July 2017) - Mortley, Raoul
ABSTRACT: Argument by analogy a major suppressed question in Plato's republic, analogy acquires an ontological significance in patristic philosophy, analogy is fundamental to law and legal argument, the will to assimilate is very strong, scientific bio-mimicry, the emphasis on mimesis, analogy in Chinese philosophy, analogy of water in chinese philosophy, analogy and difference